(untitled) (Praxis Educativa, 2020)
The educational sector has assumed long ago the challenge of incorporating technologies into teaching and learning processes. The objective of this work is to analyze the access and uses of ICT in the home of the students and in the school using the microdata of the 2016 Learning Census for seniors in high school and to show the inequalities observed by socioeconomic level of the student for type of school management and province. At the national level, The results show that although there are large disparities according to socioeconomic level in access to a computer in the home, there are no differences in access to a computer in school. In addition, there are no differences by socioeconomic level of the students in the activities proposed by the teachers to do with the computer during class time.